The emerging importance of the α-keto acid dehydrogenase complexes in serving as intracellular and intercellular signaling platforms for the regulation of metabolism - Ryan J. Mailloux (Redox Biology, 2024)
The α-keto acid dehydrogenase complex (KDHc) class of mitochondrial enzymes is composed of four members: pyruvate dehydrogenase (PDHc), α-ketoglutarate dehydrogenase (KGDHc), branched-chain keto acid dehydrogenase (BCKDHc), and 2-oxoadipate dehydrogenase (OADHc). These enzyme complexes occupy critical metabolic intersections that connect monosaccharide, amino acid, and fatty acid metabolism to Krebs cycle flux and oxidative phosphorylation (OxPhos). This feature also imbues KDHc enzymes with the heightened capacity to serve as platforms for propagation of intracellular and intercellular signaling. KDHc enzymes serve as a source and sink for mitochondrial hydrogen peroxide (mtH2O2), a vital second messenger used to trigger oxidative eustress pathways. Notably, deactivation of KDHc enzymes through reversible oxidation by mtH2O2 and other electrophiles modulates the availability of several Krebs cycle intermediates and related metabolites which serve as powerful intracellular and intercellular messengers. The KDHc enzymes also play important roles in the modulation of mitochondrial metabolism and epigenetic programming in the nucleus through the provision of various acyl-CoAs, which are used to acylate proteinaceous lysine residues. Intriguingly, nucleosomal control by acylation is also achieved through PDHc and KGDHc localization to the nuclear lumen. In this review, I discuss emerging concepts in the signaling roles fulfilled by the KDHc complexes. I highlight their vital function in serving as mitochondrial redox sensors and how this function can be used by cells to regulate the availability of critical metabolites required in cell signaling. Coupled with this, I describe in detail how defects in KDHc function can cause disease states through the disruption of cell redox homeodynamics and the deregulation of metabolic signaling. Finally, I propose that the intracellular and intercellular signaling functions of the KDHc enzymes are controlled through the reversible redox modification of the vicinal lipoic acid thiols in the E2 subunit of the complexes.